The Role of Human Parietal Area 7A as a Link between Sequencing in Hand Actions and in Overt Speech Production - Heim, Stefan; Amunts, Katrin; Hensel, Tanja; Grande, Marion; Huber, Walter; Binkofski, Ferdinand; Eickhoff, Simon B. (Frontiers in Psychology, 2012)
Research on the evolutionary basis of the human language faculty has proposed the mirror neuron system as a link between motor processing and speech development. Consequently, most work has focussed on the left inferior frontal cortex, in particular Broca's region, and the left inferior parietal cortex. However, the direct link between planning of hand motor and speech actions remains to be elucidated. Thus, the present study investigated whether sequencing of hand motor actions vs. speech motor actions has a common neural denominator. For the hand motor task, 25 subjects performed single, repeated, or sequenced button presses with either the left or right hand. The speech task was in analogy; the same subjects produced the syllable "po" once or repeatedly, or a sequence of different syllables (“po-pi-po”). Speech motor vs. hand motor effectors resulted in increased perisylvian activation including Broca's region (left area 44 and areas medially adjacent to left area 45). In contrast, common activation for sequenced vs. repeated production of button presses and syllables revealed the effector-independent involvement of left area 7A in the superior parietal lobule (SPL) in sequencing. These data demonstrate that sequencing of vocal gestures, an important precondition for ordered utterances and ultimately human speech, shares area 7A, rather than inferior parietal regions, as a common cortical module with hand motor sequencing. Interestingly, area 7A has previously also been shown to be involved in the observation of hand and non-hand actions. In combination with the literature, the present data thus suggest a distinction between area 44, which is specifically recruited for (cognitive aspects of) speech, and SPL area 7A for general aspects of motor sequencing. In sum, the study demonstrates a yet little considered role of the superior parietal lobule in the origins of speech, and may be discussed in the light of embodiment of speech and language in the motor system.